Eletriptan in the management of acute migraine: an update on the evidence for efficacy, safety, and consistent response. (September 2016) - Capi, Matilde; Curto, Martina; Lionetto, Luana; de Andrés, Fernando; Gentile, Giovanna; Negro, Andrea; Martelletti, Paolo
Migraine is a multifactorial, neurological and disabling disorder, also characterized by several autonomic symptoms. Triptans, selective serotonin 5-HT1B/1D agonists, are the first-line treatment option for moderate-to-severe headache attacks. In this paper, we review the recent data on eletriptan clinical efficacy, safety, and tolerability, and potential clinically relevant interactions with other drugs. Among triptans, eletriptan shows a consistent and significant clinical efficacy and a good tolerability profile in the treatment of migraine, especially for patients with cardiovascular risk factors without coronary artery disease. It shows the most favorable clinical response, together with sumatriptan injections, zolmitriptan and rizatriptan. Additionally, eletriptan shows the most complex pharmacokinetic/dynamic profile compared with the other triptans. It is metabolized primarily by the CYP3A4 hepatic enzyme and therefore the concomitant administration of CYP3A4-potent inhibitors should be carefully evaluated. A relatively low risk of serotonin syndrome is given by the co-administration with serotoninergic drugs. No clinically relevant interaction has been found with drugs used for migraine prophylactic treatment or other acute drugs, with the exception of ergot derivatives that should not be co-administered with eletriptan.